Teaching speed. Applying force quickly - Coonen, M. (Techniques Magazine, 2013)
Coaching and training philosophies vary among coaches. Many coaches believe that stride length plus turnover is the equation for speed. Current research indicates that these two variables are important factors when training a sprinter, but carry a secondary value when compared to their underlying causes. Research has shown that there are other variables that serve as the primary determinates of maximum speed sprinting. As a collegiate sprints coach I have incorporated training techniques that focus on improving these variables and as a result have seen outstanding development and improvement from my athletes. This article will explore current research on variables of maximal speed sprinting and how that knowledge can be applied to sprint training. Conclusion of theb author: Sprint drills, complex training, plyometrics and bounding are just four ways you can attempt to increase the forces your sprinters place on the track and limit the amount of time it takes them to do so. As a coach, you can be creative in your attempts to decrease ground contact time and increase ground contact force. Keep in mind that every exercise or drill performed should have a purpose and relate in some way to your ultimate goal, creating faster sprinters. Know the reasons behind performing every drill and make sure they are executed in a manner that benefits maximum speed development.